OS CRAVOS E A ROSA CLUBE OPERÁRIO E GRÊMIO MAGNÓLIA - INTERDEPENDÊNCIAS E TENSÕES NO INÍCIO DO SÉCULO XX EM PALMEIRA- PR - Visnieski, Danile (2014)
The quiet little town of Palmeira, in the interior of Paraná, allows through a letter that their disputes and tensions are exposed. The formation of a workers association represents more than a place of support and recreation after work, is a space of political disputes. Tensions and conflicts are evidenced throughout the dance of a society that is reconstructed from the early twentieth century, all printed by period changes have not gone unnoticed by the local elite, who insists on remaining in their dominant role and refuses to legitimize representativeness of the new individuals who come to occupy their roles in the political and social landscape of small Palmeira.